Integrating renewable energy into Nigeria’s energy supply mix - Nuhu Caleb Amulah (Renewable Energy and Sustainable Development, 2022)
In this paper, simulation model for Nigeria’s energy system is developed using EnergyPLAN simulation tool to study the structure of the present energy system and explore alternative future scenarios based on renewable energy sources. First, 2017 reference scenario was developed and validated to reflect Nigeria’s energy supply and consumption in 2017. Two other future scenarios were then developed; the 2030 REMP scenario to show a pathway to achieving the Renewable Energy Master Plan target of increasing the supply of renewable electricity by 36% of the total electricity generation by 2030; and the 2050 RE scenario which seeks to increase the share of renewable energy by >70% of the total electricity generation and introduces the concept of electric vehicles and the use of biofuel in the transport sector. Both the 2030 REMP and the 2050 RE scenarios employed the National Energy Master Plan 7% reference growth scenario for all sectors using 2017 as the base year. The study shows with the abundance of renewable energy sources in Nigeria, it is possible to develop an energy system that is sorely dependent on renewable energy. The 2030 REMP shows the shift from fossil fuel power plant to renewable energy for electricity generation will result in an increase in the share of renewable energy in electricity production from 20.2% in 2017 to 37.88% in 2030 while the 2050 RE shows that the share can go up to 71.20% if proper policies and infrastructures are put in place.   Received: 25 March 2022 Accepted: 13 April 2022 Published: 16 May 2022